Smart tourism: a scientometric review (2008-2020) - Borges-Tiago, Teresa; Veríssimo, José; Tiago, Flávio (European Journal of Tourism Research, 2021)
The fast path of smart tourism developments within the tourism and hospitality field clarifies the need to identify its intellectual structures and monitor its evolution. 43% of the articles ever published are from the last two years. An initial work, covering the papers published between 2008 and 2018, reveal five dimensions under a humanware approach: (i) smart technologies; (ii) smart ecosystems; (iii) value creation; (iv) tourism experience; and, (v) sharing economy. With this classification framework, the present work aims to identify emerging trends and future research paths using a scientometric analysis of smart tourism research from 2008 to 2020. The scientometric analysis was conducted over the 1321 papers referenced and retrieved from Web of Science and Google Scholar, narrowed to the 225 classified as tourism and hospitality. These articles were subject to content, citation and authorship analysis. The content analysis produced eight clusters that represent the main research streams. This result confirms the field's fast evolution path since two of these clusters emerged in the last three years. The twenty most cited articles were reviewed and classified under the humanware framework. The vast majority of the works are still related to smart ecosystems and technologies, unveiling the need to enrich knowledge related to the other streams and the tourism and hospitality response to Covid-19 supported by smart technologies.